Hubungan Lingkungan Kerja Perawat dengan Gaya Kepemimpinan Kepala Ruangan di Rumah Sakit Sumber Kasih Kota Cirebon - Norma Mardiani (Jurnal Soshum Insentif, 2018)
The era of free market resulting in the high competition in the service sector health including hospital.Efforts to the maintaining the quality of services in the hospitals were not separated from the role of important profession nursing because power nursing be in order leading service, , so it needs environmental design work conducive and support, motivation, briefing off leaders so nurse can work effectively and efficiently. The purpose of this research is to find relations work environment a nurse with style leadership in a hospital Sumber Kasih Cirebon 2017. The kind of research used descriptive correlation and design peneliatian cross sectional.tehnink sampling used is random sampling with 49 sampel. Data collection uses a questionnaire. Analysis data using the rank spearmen. Based on the results of management of data by spss to test the correlation between work environment to the style of leadership obtained value a correlation coefficient rank spearmen of 0,306 with the sig. ( 2-tailed ) as much as 0,032. Because the value of sig. ( 2-tailed ) & lt; 0.05 so h0 which states that nobody a significant relation between relations work environment to the style of leadership rejected. Thus can be concluded that a significant relation exists between work environment a nurse with style leadership in the hospital Sumber Kasih. Advice provided in this research let RS Sumber Kasih Cirebon can create, increase while keeping a working relationship and all work among colleagues and their superior.